DASH: a smart platform for new-driver progress with future-ready AI integration - Mohd Suhaimi, Nur Syauqina; Abdul Halim, Izzah Inani (Universiti Teknologi MARA, Perak, 2025)
The integration of Artificial Intelligence (AI) in mobile application development has significantly enhanced mobile computing services for end users. AI provides intelligent support and enables users to manage various mobile app functionalities automatically. In the context of assessing eligibility for obtaining a driving license, the Driving Academy - Schedule Hour (DASH) platform was developed to support key stakeholders, including the Road Transport Department (RTD) Malaysia, driving academies, and prospective drivers. DASH offers features that assist academy administrators, instructors, and students by serving as a centralized hub to track accumulated driving training hours and monitor progress toward test eligibility. Developed using the Flutter framework and Firebase and designed to run on mobile devices for end users and a web page for administrators, DASH addresses the need for real-time access to training progress for students and simplifies test management for administrators prior to official driving license issuance. Future developments of DASH will focus on integrating advanced artificial intelligence capabilities, including predictive analytics and adaptive learning models, to enhance user experience, optimize performance, and support intelligent decision-making within the mobile environment.